The Value of Nature: Utilitarian Perspective - Udoudom, Mfonobong (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Utilitarianism regards pleasure, or the satisfaction of interest, desire, and preference as the only intrinsic value. Therefore, Utilitarian’s believes that right actions are those which produce the greatest pleasure for the greatest number of people. Ethical actions are judged and determined by their consequences, as opposed to de-ontological, which is concerned with rights and duties regardless of consequences. It focuses is on the instrumental value of actions. However, in environmental ethics, instrumental value also comprises the value of nature as a human resource. Ascribing the instrumental value to nature had started with humans' use of natural resources for survival on earth. Human use of natural resources soon turned into the exploitation of nature through a rapidly changing process which includes the science and technological revolution. Thus, the anthropocentric worldview was blamed for human reckless exploitation of nature. Anthropocentricism; a dominant western worldview sees only human beings as having independent moral status even to the detriment of other beings in the environment. This theory prioritizes those attitudes, values, or practices which give preferences to human interests rather than the interests of beings who are other than humans in the environment. In this work, I will be discussing instrumental value. I will be discussing the value of nature only as an instrument of human welfare for life support. I will be preoccupied with some of the issues regarding whether nature has any interest or significance as such independently of human concern.